Das System der russischen Kollektivsymbolik Eine empirische Untersuchung - Fleischer, Michael (Specimina philologiae Slavicae, 1997)
In the present work it is next to the actual goal, i. the determination of the collective symbols, the determination of their hierarchy and semantization, and also a test of the method itself. What services does the method perform, how powerful is it when it comes to determining a complex and complicated object of culture in its form and function , In order to enable comparisons specific to individual cultures, the study was also carried out for Polish and German culture (see Fleischer 1995 and 1996). The entire analysis is in the context of the system-theoretical cultural theory established by the author in 1989 (Fleischer 1989 and 1994), whose examination represents the analysis. It is therefore a theory-based, system-theoretical-constructivist work, which is to examine the hypotheses and the predictions of the theory.